Jujube as a Florida Fruit Crop - Kevin M. Folta; Dustin Huff; Ali Sarkhosh (EDIS)
Despite being cultivated in China for millennia, the Chinese jujube is mostly unknown to Western consumers. The fruits are borne from vigorous trees that are tolerant to drought and other stresses, as well as disease. A number of cultivars have been demonstrated to produce in Florida. This publication is a review of jujube genetics and management as this crop gains favor among growers on small farms and home growers.